Dinamika Konvergensi Peran Perempuan Di Era Ekonomi Digital - Dini Amalia (Al-Musthofa: Journal of Sharia Economics, 2018)
Economy in Indonesia has rapidly increased especially for these latest ten years. The massive explosion of technological innovation already put the huge influence in any economical aspects which then emerges the new era of digital economy. This phenomenon¸unavoidably also pushes women to come up out of their comfort zone. Women are no longer merely trapped on the discourse of domestic area. They turn up as more multitasking and multitalented community. The problem arouse then is about they having the convergence role to survive in this new era. In this paper, the convergence role of women particularly living around the challenges in digital economy era will be revealed through any concerns on the dual role of women in the midst of any upgradings toward internet-based technology. All the improvements give women a lot of priceless opportunities and meticulous challenges at once. Mostly women fit their new role not only to fix household buat also to actively engaged to economic field. They take chance to bring up a reliable position as more qualified, productive and innovative leader in business. At the same time, women take the challenges to propose the convergence role to build the identity as modern women, not only urged to be independent and competitive but also keep inspiring for struggling and surviving their potentials and hybrid identity.